Hubungan Antara Self Control dengan Smartphone Addiction pada Mahasiswa Jurusan Akuntansi - Okfrima, Ria; Utama, Tari Mulfika; Ade, Frihapma Semita (SAFE-Network, 2024)
This study aims to determine the relationship between Self Control and Smartphone Addiction in students majoring in Accounting Class 18 Universitas Putra Indonesia YPTK Padang. The independent variable in this study is Self Control and the dependent variable is Smartphone Addiction. The measuring instrument used in this research is the Self Control scale and the Smartphone Addiction scale. The sampling technique in this study used the Simple Random Sampling technique. The sample in this study was 147 students majoring in Accounting, class 18, Universitas Putra Indonesia YPTK Padang. The validity and reliability test in this study used the Cronbach Alpha technique. The item discriminatory index on the Self Control scale moves from rix = 0.341 to rix = 0.599 with a reliability coefficient of = 0.908. While on the Smartphone Addiction scale, it moves from rix = 0.329 to rix = 0.613 with a reliability coefficient of = 0.909. Based on the results of data analysis, it can be concluded that there is a significant relationship between Self Control and Smartphone Addiction, with a correlation value (r) of -0.394 with a significant level of 0.000 which means the hypothesis is accepted. This shows that there is a significant negative relationship between Self Control and Smartphone Addiction in Accounting students class 18, Universitas Putra Indonesia YPTK Padang.